2018
DOI: 10.1515/jpem-2018-0233
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes in pediatric differentiated thyroid carcinoma

Abstract: Background Until the American Thyroid Association (ATA) guidelines on management of pediatric differentiated thyroid carcinoma (DTC) became available in 2015, all children with DTC were treated like adults. This study aims to investigate the outcome of pediatric DTC and factors predicting the response to therapy in pediatric DTC managed according to adult guidelines. Methods Clinical records of 41 children less than 18 years of age diagnosed with DTC followed from 2007 in a single center were reviewed. Accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Instead, the role of sTg in DTC pediatric patients remains to be fully established [12][13][14][15]. At the same time, the usefulness of ATA risk classification in children with DTC has been evaluated in few studies [16][17][18][19][20][21], and also the 1-year response to initial therapy categories presented in the 2015 adults' guideline (i.e., excellent response, biochemical incomplete response, structural incomplete response and indeterminate response) [3] has been tested few cases of pediatric population.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the role of sTg in DTC pediatric patients remains to be fully established [12][13][14][15]. At the same time, the usefulness of ATA risk classification in children with DTC has been evaluated in few studies [16][17][18][19][20][21], and also the 1-year response to initial therapy categories presented in the 2015 adults' guideline (i.e., excellent response, biochemical incomplete response, structural incomplete response and indeterminate response) [3] has been tested few cases of pediatric population.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the rarity of thyroid carcinoma in children and ethical concerns surrounding the clinical trials in such a population of underage patients, it is di cult to carry out prospective randomized clinical trial. Bhavani et al [12] recently reported that DTC in children managed according to adult guidelines had a good cure rate. As a result, this project retrospectively analyzed the clinical data of 54 children (aged ≤ 18) with PTC consecutively enrolled within the last 8 years, and followed-up, only then did we believe that the majority of pediatric PTC should perform TT, routine prophylactic CND and Therapeutic LND.…”
Section: Introductionmentioning
confidence: 99%
“…Though multiinstitutional trials as well as large series have depicted the clinicopathological profile, outcomes of surgical management and the risk factors for persistent and metastatic disease among pediatric thyroid cancers, literature from India has been limited to case reports. To the best of our knowledge, there are only three published academic institution reports on pediatric/adolescent thyroid cancers from India, among them only one study included children \ 18 years of age (pediatric population) [12][13][14]. Therefore, we conducted this study to perceptionalize the clinicopathological profile and outcomes of management among children with PTC in India.…”
mentioning
confidence: 99%